Powerful Interactions How to Connect with Children to Extend Their Learning, Second Edition. - Dombro, Amy Laura (National Association for the Education of Young Children, 2020)
Make your everyday interactions with children intentional and purposeful with these steps: Be Present, Connect, and Extend Learning.